Long-Term Observation of Higher-Order Aberrations and Microdistortions in Bowman’s Layer After Small Incision Lenticule Extraction for the Correcting Myopia With Spherical Equivalent Higher Than −9.0 Diopters - Zhou, Xueyi; Qin, Bing; Han, Tian; Shang, Jianmin; Chen, Zhuoyi; Zhao, Jing; Yao, Peijun; Zhou, Xingtao (Frontiers in Medicine, 2022)
Purpose: To evaluate the outcomes in corneal higher-order aberrations (HOAs) and microdistortions in the Bowman’s layer after femtosecond laser small incision lenticule extraction (SMILE) for correcting extremely high myopia. Methods: This prospective study included patients with myopia with spherical equivalent ≥-9.0 Diopters (D). SMILE was performed in forty eyes of 40 patients. Pentacam was used to evaluate HOAs before and at 1 day, 3 months, 6 months, and 2 years after surgery. Fourier-domain optical coherence tomography was used to evaluate microdistortions at 2 years postoperatively. Thirty-two eyes of 32 patients receiving femtosecond laser-assisted in situ keratomileusis (FS-LASIK) were enrolled as the control group. HOAs were measured before, at 1 day and at least 1 year postoperatively. Results: After SMILE, the long-term safety and effectiveness index was 1.25 and 0.85, respectively. Microdistortions were observed in 73.5% of the eyes at 2 years, with an average number of 1.20±1.22 microdistortions and an average width of 287.37±259.00 µm. We detected more microdistortions in the horizontal meridian than in the vertical meridian (p=0.035). The average number and width of microdistortions were both higher in the central region (≤4 mm) than in the peripheral region (4–8 mm) (both p<0.001). With the exception of horizontal trefoil in the SMILE group and vertical trefoil in the FS-LASIK group, significant changes over time were observed in all other HOAs (all p<0.05). Meanwhile, we detected significant increases in the total corneal HOA, spherical aberration (SA), and coma at all time-points after both surgeries (all p<0.01). Compared with FS-LASIK, SMILE induced less SA (p<0.001) and more horizontal coma (p=0.036). In the SMILE group, the HOA, SA, and trefoil were more in the small optical zone (≤6.0 mm) than in the large optical zone (>6.0 mm) (all p<0.05). The increase in SA and most trefoil correlated with the mean number of central microdistortions number (all p<0.05). Conclusion: For myopia over -9.0D, the microdistortions in the Bowman’s layer were still detectable in most eyes long-term after SMILE. Both SMILE and FS-LASIK induced more HOAs, mainly HOA, SA, and coma. The small optical zone and microdistortions may affect postoperative aberrations.